The impact of planning on developing human resources performance - An applied study on Al-Manna Trading, Investment, Contracting and Building Company 2020 – - Hassan, Mahamat Boukhari; Al-Catib, Mahamat Bachar (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims: to know whether the company is applying the proper management planning process or not, to know the planning methods used in the company, to know the obstacles that the company faces when using the management planning process and to find scientific results that can be used when carrying out the planning process.The study followed the descriptive, analytical method to analyze the questionnaire data.The most important findings of the study are: There is a positive relationship of statistical significance between planning and developing human resources performance, good planning leads to development of human resources performance in the company, strategic planning helps in the development of human resources performance in the company and human resources plans are modified according to the changes that occur in the company’s environment.The study recommends the following: The leader of the company must involve human resources in setting goals and drawing plans. The company should work with planning to increase its marketing share. The company should double its interest in planning in order to achieve its goals effectively, and involve employees in continuous training in order to develop the company.
Keywords: impact; planning; performance; resources; human